The interplay between host innate immunity and hepatitis E virus - Li, Yang; Qu, Changbo; Yu, Peifa; Ou, Xumin; Pan, Qiuwei; Wang, Wenshi (Viruses, 2019)
Hepatitis E virus (HEV) infection represents an emerging global health issue, whereas the clinical outcomes vary dramatically among different populations. The host innate immune system provides a first-line defense against the infection, but dysregulation may partially contribute to severe pathogenesis. A growing body of evidence has indicated the active response of the host innate immunity to HEV infection both in experimental models and in patients. In turn, HEV has developed sophisticated strategies to counteract the host immune system. In this review, we aim to comprehensively decipher the processes of pathogen recognition, interferon, and inflammatory responses, and the involvement of innate immune cells in HEV infection. We further discuss their implications in understanding the pathogenic mechanisms and developing antiviral therapies.